The impact of development financial aid provided to Syria on the Domestic Resources Gap - ابراهيم فادي; رضوان العمّار; هيفاء غدير (Latakia University Journal - Economic and Legal Sciences Series, 2022)
This research aims to study the impact of development financial aid on the Domestic Resources Gap in Syria during the period 2000-2019. Where the study of the long-term relationship between the development financial aid provided to Syria and the Domestic Resources Gap was based on the Johansen Cointegration Test, and on the (VECM) model to verify the direction of the causality of the long-term relationship, and the Causal Granger test to verify the existence of the short-term relationship, and the impact of the development financial aid provided to Syria on the Domestic Resources Gap was discovered through Impulse Response Functions (IRF) and Forecast Error Variance Decomposition (FEVD). Whereas, the results of the Johansen Cointegration Test showed that there is a long-term relationship between the development financial aid provided to Syria and the Domestic Resources Gap during the period 2000-2019. Whereas, the VECM model indicated that there is a long-term and two-way causal relationship between the development financial aid provided to Syria and the Domestic Resources Gap. As for the results of the Causal Granger test, they matched the results of the VECM model with regard to the short-term relationship, as the results of these two tests showed that there is a short-term relationship between the development financial aid provided to Syria and the Domestic Resources Gap during the period 2000-2019. The IRF and FEVD showed that there is an impact of the development financial aid provided to Syria on the Domestic Resources Gap, but this effect was very weak.